Clinical Profile and Antibiotics Sensitivity in Childhood Urinary Tract Infection at Dhulikhel Hospital - Singh, SD; Madhup, SK (Kathmandu University Medical Journal, 2015)
Background Urinary Tract Infection implies presence of actively multiplying organisms in the urinary tract. Although it is infrequently associated with mortality, it is still a significant cause of morbidity. Early diagnosis is critical to preserve renal function of growing kidney.Objective Our purpose was to determine the clinical, microbiologic profile and antibiotic sensitivity of such infections in pediatric Urinary Tract Infection (UTI) patients at Dhulikhel Hospital.Methods A hospital based prospective descriptive study of 135 children from 2 months to 16 years, with clinical diagnosis of urinary tract infection who visited the pediatric department of Dhulikhel Hospital over the period of 15 months were enrolled in the study. All patients underwent routine urine analysis and culture. Children with recurrent UTI underwent micturating cystourethrogram (MCUG). Children with recurrent UTI of more than two years and with feature of pyelonephritis underwent USG abdomen as well. Complications and response of the treatment was observed in all cases of UTI. All data were entered in Epidata and data analysis was done using spss 16 version.Results Among 135 children, 32.5% were male and 67.4% were female. Fever was the most common presenting symptom in 74.80% of patients followed by dysuria in 54.1%. Among these children 95.6% had significant pyuria and 45% had culture positive infection. Children who showed positive for bacteriuria, Escherichia coli (78.7%) was the most common organism and are more than 80% sensitive to Amikacin, Gentamicin, Ceftriaxone, Ofloxacin, Nalidixic acid, Imipenem and Vancomycin. Co-trimoxazole was the most common drug used for treatment with a mean drug respond time of (mean±S.D) of 2.21±.78 days. 2±±. Children who had recurrent UTI were more prone to develop culture positive UTI (p=0.0001).Conclusion Urinary Tract Infection in female was almost twice more common than in male. Co-trimoxazole was the most common drug used for treatment, sensitivity of this drug was less than 50% for all organisms.Kathmandu Univ Med J 2013; 11(4): 319-324